Monetary Policy Effect on Private Sector Investment: Evidence from Sierra Leone - Brima, Sesay; Brima, Abdulai Salia (International Journal of Economics and Financial Issues, 2017)
Private sector investment has become an increasingly significant objective for the government of Sierra Leone in promoting economic growth and enhancing job creation, and monetary policy has always been one of the main economic management tools that governments use to shape economic performance. The study therefore examines the rate at which changes in monetary policy in Sierra Leone has affected the behavior of private sector investments, theories and empirical studies are reviewed in a way to identify a suitable model for private sector investment for the period 1980 to 2014. Using recent econometric techniques, the results suggest that money supply and gross domestic saving exert positive and statistically significant effect on private sector investments whereas Treasury bill rate, inflation and gross domestic debt exert a negative effect. An important policy implication emerging from this study is to facilitate the establishment of financial institutions to increase credit delivery to the private sector so as to enhance private investment. Keywords: Monetary policy, Private sector investment, Sierra Leone. JEL Classifications: E52, E58, E220